2021
DOI: 10.3389/fgene.2021.698590
|View full text |Cite
|
Sign up to set email alerts
|

Association Between MTHFR Polymorphisms and the Risk of Essential Hypertension: An Updated Meta-analysis

Abstract: Background: Since the 1990s, there have been a lot of research on single-nucleotide polymorphism (SNP) and different diseases, including many studies on 5,10-methylenetetrahydrofolate reductase (MTHFR) polymorphism and essential hypertension (EH). Nevertheless, their conclusions were controversial. So far, six previous meta-analyses discussed the internal relationship between the MTHFR polymorphism and EH, respectively. However, they did not evaluate the credibility of the positive associations. To build on pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 125 publications
0
13
0
Order By: Relevance
“…Several studies performed in non-African countries also demonstrated that genotype TT or T allele of rs1801133 may increase the risk of HTN (Fan et al, 2016;Bouzidi et al, 2020;Wu et al, 2022). The discrepancies observed between these studies may be due to geographical location, ethnicity, and epigenetic mechanisms that are involved in the regulation of MTHFR gene expression (Fu et al, 2019;Meng et al, 2021). Suggesting that data linking HTN to rs1801133 remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies performed in non-African countries also demonstrated that genotype TT or T allele of rs1801133 may increase the risk of HTN (Fan et al, 2016;Bouzidi et al, 2020;Wu et al, 2022). The discrepancies observed between these studies may be due to geographical location, ethnicity, and epigenetic mechanisms that are involved in the regulation of MTHFR gene expression (Fu et al, 2019;Meng et al, 2021). Suggesting that data linking HTN to rs1801133 remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The above association became less reliable after FPRP, BFDP, and Venice criteria tests. False positives may exist and should be further verified [ 42 ]. Both studies showed no significant association between MTHFR A1298C polymorphism and hypertension [ 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…False positives may exist and should be further verified [ 42 ]. Both studies showed no significant association between MTHFR A1298C polymorphism and hypertension [ 41 , 42 ]. However, those meta-analyses only studied essential hypertension and did not focus on the association between MTHFR polymorphisms and the susceptibility to H- type hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…11 The alteration of MTHFR activity is caused by several mutations in the MTHFR gene. 12 The MTHFR gene, which is found on chromosome 1 (1p36.3), encodes a 77 kDa dimeric protein that is the rate-limiting enzyme in the methyl cycle. 13 MTHFR catalyses only one biochemical reaction: the formation of 5-methylenetetrahydrofolate, a cosubstrate for the remethylation of Hcy to methionine.…”
Section: Introductionmentioning
confidence: 99%
“…13 MTHFR catalyses only one biochemical reaction: the formation of 5-methylenetetrahydrofolate, a cosubstrate for the remethylation of Hcy to methionine. 12 MTHFR C677T (C substitution at base pair 677) is a common MTHFR gene mutation that causes alanine to be replaced by valine at position 222 of the encoded protein product. 14 Previous research has linked TT variants of the MTHFR C677T polymorphism to elevated serum Hcy concentrations and the severity of ischaemic stroke, implying an important role as a marker of ischaemic stroke.…”
Section: Introductionmentioning
confidence: 99%